Prototype of grid tension monitoring system - Muhammad Saiful Amin, Mohd Suhaimi (2022)
This project is aimed at developing a prototype of grid tension monitoring system on overhead transmission line. The reason behind this project is to create a real-time monitoring system for grid tension overhead transmission line temperature, sag axis and electrically powered current value. Sagging on the transmission line can damage the transmission tower, this project aims to monitor the sag and scheduled the maintenance before further damage can be done to the transmission tower and transmission line. As accidents are constantly being reduced and diagnoses are accelerating for automated grids, real-time remote sensing and control is the configurations for smart grid implementation. In case of malfunction, the voltage and current exceed the operating limit, which requires in-time monitoring as well as diagnosis reporting. This paper aims at creating a monitoring system for the purpose analyzing and maintenance. This will prevent over sagging of transmission line thus making maintenance safe to carry out and possible before any further damage. This project also provides overhead tracking monitoring framework for an industry analyst or professionals. This is accomplished by using the combination of sensors and microcontroller.